Farmakokinetika antikoagulacijskih zdravil pri jetrni in ledvični disfunkciji - Grabnar, Iztok (Farmacevtski vestnik, 2014)
Atrial fibrilation is a major cause of morbidity and mortality and requires long-term anticoagulation treatment. For more than 50 years warfarin was the only oral anticoagulation drug available. however, treatment with warfarin is very challenging. The limitations of warfarin treatment prompted the development of novel oral anticoagulant drugs with direct mechanism of action and sufficiently wide therapeutic window to allow for fixed-dose administration without the need for routine therapeutic monitoring. Recently three novel anticoagulant drugs (dabigatran, rivaroxaban, and apixaban) have been approved, which are a viable alternative to warfarin. This review summarizes their pharmacokinetics and pharmacodynamics and gives an overview of the dosing recommendations in patients with renal and hepatic impairment.
Keywords: antikoagulacijsko zdravljenje; dosing recommendation; jetrna bolezen; klinična farmakokinetika; ledvične bolezni; liver disease; novejša antikoagulacijska zdravila; novel art anticoagulant drugs; priporočila za odmerjanje; renal disease